Surface Electromyography (EMG) Signal Acquisition - Siti Hajar bt Mat Jam, Siti Hajar (Universiti Teknologi Petronas, 2010)
The aim of this project is to develop technology to acquire signal from the surface electromyography based on the muscle activity. SEMG, the Surface Electromyography, is a non-invasive technique aimed at detecting and/or inferring EMG signal acquired from surface of the skin underlying the human muscle. In this research, the signal is analyzed using MATLAB was created to study on the EMG signal acquired.